2011
DOI: 10.2466/02.09.15.16.pr0.109.5.573-599
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Posttraumatic Stress Disorder in U.S. Combat Veterans: A Meta-Analytic Review

Abstract: Among U.S. veterans who have been exposed to combat-related trauma, significantly elevated rates of posttraumatic stress disorder (PTSD) are reported. Veterans with PTSD are treated for the disorder at Veterans Affairs (VA) hospitals through a variety of psychotherapeutic interventions. Given the significant impairment associated with PTSD, it is imperative to assess the typical treatment response associated with these interventions. 24 studies with a total sample size of 1742 participants were quantitatively … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
75
2
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(83 citation statements)
references
References 67 publications
(96 reference statements)
5
75
2
1
Order By: Relevance
“…An exception is the trial by Nacasch et al (2010), which found large between-group effect sizes at posttreatment and follow-up (d =1.80 and d = 2.10, respectively) although, again, the comparison condition (psychodynamic therapy) does not have empirical support as a treatment for PTSD and the sample size was small (N=30). A recent meta-analysis of 24 studies of PTSD treatment with VA patients (N= 1742; consisting of evidence-based and non-evidence-based treatments, as well as inpatient and outpatient group and individual therapy) showed medium between-group effect sizes (d = 0.48) for active treatments vs controls, suggesting that patients in active therapies fared better than 66% in control conditions (Goodson et al, 2011). Unfortunately however, all effect sizes were calculated based on completers only, which substantially inflates treatment effects.…”
Section: Summary Of Findings From Outcome Studiesmentioning
confidence: 95%
“…An exception is the trial by Nacasch et al (2010), which found large between-group effect sizes at posttreatment and follow-up (d =1.80 and d = 2.10, respectively) although, again, the comparison condition (psychodynamic therapy) does not have empirical support as a treatment for PTSD and the sample size was small (N=30). A recent meta-analysis of 24 studies of PTSD treatment with VA patients (N= 1742; consisting of evidence-based and non-evidence-based treatments, as well as inpatient and outpatient group and individual therapy) showed medium between-group effect sizes (d = 0.48) for active treatments vs controls, suggesting that patients in active therapies fared better than 66% in control conditions (Goodson et al, 2011). Unfortunately however, all effect sizes were calculated based on completers only, which substantially inflates treatment effects.…”
Section: Summary Of Findings From Outcome Studiesmentioning
confidence: 95%
“…The Veterans Health Administration (VHA), the health care arm of the U.S. Department of Veterans Affairs, annually provides health care to more than 500,000 veterans diagnosed with PTSD (Hoff et al 2013). A substantial body of research with both veterans and non-veterans has demonstrated the efficacy of trauma-focused psychotherapies for PTSD (Bisson et al 2007;Goodson et al 2011;Haagen et al 2015;Institute of Medicine 2007). These treatments produce clinically meaningful reductions in 49-70 % of veterans, although they often do not result in complete remission (Steenkamp et al 2015).…”
Section: Introductionmentioning
confidence: 98%
“…We were able to follow up over 80% of those offered the treatment at six months. This compares favourably with similar PTSD treatment programmes offered to military veterans in different countries (Forbes et al, 2008a;Richardson et al, 2011;Goodson & Helstrom, 2011;Currier et al, 2014). Further, we are confident that no differences were present between individuals that it was possible to review at six months and those lost to follow up (Murphy et al, 2015).…”
Section: Strengths and Limitationsmentioning
confidence: 71%
“…The picture from US studies is mixed with older programmes that had less emphasis on individual trauma therapy and a greater reliance on group sessions demonstrating significant improvements but that these are not always maintained at follow up (Johnson et al, 1996;Goodson & Helstrom, 2011;Currier, Holland Drescher, 2014;Hammarberg & Silver, 1994;Fontana & Rosenheck, 1997). More recently, US researchers have demonstrated the efficacy of using Cognitive Processing Therapy (CPT) for veterans with PTSD (Morland et al, 2014;Chard, Schumm, Owens, & Cottingham, 2010;Monson et al, 2006).…”
mentioning
confidence: 99%